Investigation of mould design and process parameter optimisation of plastic injection moulding for thin wall part - Hussin, Azmee (2019)
In plastic injection moulding industries such as automotive, packaging and medical, demands for thin wall parts increases for the reason of light weight, lower cycle time, lower part cost and higher productivity. However, a lot of challenges faced by the moulders since the mould and processing parameters are critical to produce good quality of thin wall parts. This research describes the mould design and process parameter aspects of thin wall part focusing on tubular shape The aim of the research is to investigate the factors that influence the moulded part quality in terms of part shrinkage and weight. The research begin with development of mould for a polypropylene thin wall tubular part and followed by study on the effect of injection moulding process parameter towards moulded part quality. In order to identify the moulding parameters that influences the moulded part quality, Taguchi optimisation method was employed in the research. Based on the obtained simulation result, the preferred size of runner was diameter of 4 mm, gate size was 1 mm and the gate number was 4 number for actual mould fabrication. On the effect of injection pressure, the result shows that with increasing in injection pressure the part shrinkage reduced and part weight increased. As for the effect of melt temperature, the result shows that with increasing in melt temperature the part shrinkage increased and part weight reduced. As for the optimisation, the result shows that temperature contributed significantly to shrinkage and weight of moulded part. Mould temperature have significant effect to outer diameter shrinkage while melt temperature have significant effect to inner diameter shrinkage.